PRODUCTIVE ZAKAT PROGRAM RENEWAL MODEL TO INCREASE MUSTAHIQ EMPOWERMENT (CASE STUDY OF KOLAKA DISTRICT BAZNAS) - Wandha Audia Magfirah; Try Ayu Puspita Ningsih; Sri Putri Ayu (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2023)
Productive zakat is a form of utilization of zakat. So, the distribution is productive, namely to add to or as business capital for mustahiq. That mustahiq must return business capital, that is in nature as a strategy to educate them to work hard so that their business is successful. The purpose of this study is to describe the productive zakat program renewal model implemented by BAZNAS Kab. Kolaka to increase the empowerment of mustahiq. We will explore how efforts are made in the productive zakat program, including business assistance, access to capital, and social network development. The research method used by researchers is a qualitative approach with descriptive methods. that BAZNAS Kab. Kolaka could not renew the productive zakat program because the program could not be realized because it was constrained by insufficient income of zakat funds so that it could not realize the productive zakat program. However, BAZNAS Kab. Kolaka is working on a small scale by channeling business funds whose business is named (Zmart) which will become the forerunner of the productive zakat program. The implication of this research is that the authors expect participation and public awareness in order to realize this productive zakat program.